2018
DOI: 10.1111/aor.13349
|View full text |Cite
|
Sign up to set email alerts
|

LVAD Pump Flow Does Not Adequately Increase With Exercise

Abstract: Left ventricular assist devices (LVADs) restore cardiovascular circulatory demand at rest with a spontaneous increase in pump flow to exercise. The relevant contribution of cardiac output provided by the LVAD and ejected through the aortic valve for exercises of different intensities has been barely investigated in patients. The hypothesis of this study was that different responses in continuous recorded pump parameters occur for maximal and submaximal intensity exercises and that the pump flow change has an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“… EmaxL : among all the investigated parameters, EmaxL is one of the most important in assuring a higher TCO at exercise. These results are in line with previous clinical studies evidencing the crucial role of the residual LV function in eliciting a higher TCO and exercise capacity . Noor et al observed that patients with a residual LV contractility are able to better accommodate an increase in TCO, resulting in higher exercise capacities.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“… EmaxL : among all the investigated parameters, EmaxL is one of the most important in assuring a higher TCO at exercise. These results are in line with previous clinical studies evidencing the crucial role of the residual LV function in eliciting a higher TCO and exercise capacity . Noor et al observed that patients with a residual LV contractility are able to better accommodate an increase in TCO, resulting in higher exercise capacities.…”
Section: Discussionsupporting
confidence: 91%
“…The increased HR and LV preload resolved in a higher Q AV (+0.5 L/min) while only a minimal increase in Q LVAD (+0.1 L/min). This rather mild relationship between HR and Q LVAD during exercise is in agreement with previous clinical observations . Regardless of the individual contribution of the LV and the LVAD, simulations evidenced that an increase in HR does translate ultimately in an increase in TCO (+0.7 L/min).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations